Bacteriophage therapy for infections in CF. (12th January 2021) - Chan, Benjamin K.; Stanley, Gail; Modak, Mrinalini; Koff, Jon L.; Turner, Paul E.
Abstract: Pseudomonas aeruginosa and Staphylococcus aureus are bacterial pathogens frequently associated with pulmonary complications and disease progression in cystic fibrosis (CF). However, these bacteria increasingly show resistance to antibiotics, necessitating novel management strategies. One possibility is bacteriophage (phages; bacteria‐specific viruses) therapy, where lytic phages are administered to kill target bacterial pathogens. Recent publications of case reports of phage therapy to treat antibiotic‐resistant lung infections in CF have garnered significant attention. These cases exemplify the renewed interest in phage therapy, an older concept that is being newly updated to include rigorous collection and analysis of patient data to assess clinical benefit, which will inform the development of clinical trials. As outcomes of these trials become public, the results will valuable gauge the potential usefulness of phage therapy to address the rise in antibiotic‐resistant bacterial infections. In addition, we highlight the further need for basic research to accurately predict the different responses of target bacterial pathogens when phages are administered alone, sequentially, or as mixtures (cocktails), and whether within‐cocktail interactions among phages hold consequences for the efficacy of phage therapy in patient treatment.